2009
DOI: 10.1590/s1517-83822009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the rRNA genes of Babesia spp and Ehrlichia canis detected in dogs from Ribeirão Preto, Brazil

Abstract: The partial DNA sequences of the 18S rRNA gene of Babesia canis and the 16S rRNA gene of Ehrlichia canis detected in dogs from Ribeirão Preto, Brazil, were compared to sequences from other strains deposited in GenBank. The E. canis strain circulating in Ribeirão Preto is identical to other strains previously detected in the region, whereas the subspecies Babesia canis vogeli is the main Babesia strain circulating in dogs from Ribeirão Preto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…vogeli isolate in this study clustered in the same subclade as strains found in dogs from the states of São Paulo and Minas Gerais and from countries belonging to different continents, such as Venezuela, Nigeria, South Africa, Egypt and China (Matjila et al 2004, Passos et al 2005, Rey-Valeirón et al 2007, Sasaki et al 2007, Oliveira et al 2009, Xu et al 2015 (Fig.3).…”
Section: Discussionsupporting
confidence: 64%
“…vogeli isolate in this study clustered in the same subclade as strains found in dogs from the states of São Paulo and Minas Gerais and from countries belonging to different continents, such as Venezuela, Nigeria, South Africa, Egypt and China (Matjila et al 2004, Passos et al 2005, Rey-Valeirón et al 2007, Sasaki et al 2007, Oliveira et al 2009, Xu et al 2015 (Fig.3).…”
Section: Discussionsupporting
confidence: 64%
“…The first molecular detection of E. canis in Brazilian cats was reported in a study at a VTH of Minas Gerais State, Southeastern Brazil, in which blood samples from 3/15 cats tested positive by nested-PCR for the 16S rRNA gene. The E. canis sequence, a fragment of the 16S rRNA gene, showed 100% identity with the E. canis sequence obtained from dogs from the same study area (OLIVEIRA et al, 2009a(OLIVEIRA et al, , 2009b. Further studies are needed to better characterize the Ehrlichia spp.…”
Section: Ehrlichiosis In Catsmentioning
confidence: 92%
“…Ehrlichiosis is widely detected across Brazil (Figure 3). Three species have been described to date in Brazil: E. canis (AGUIAR et al, 2007a;LABRUNA et al, 2007;UENO et al, 2009;DINIZ et al, 2007;OLIVEIRA et al, 2009a), E. ewingii (OLIVEIRA et al, 2009c) and E. chaffeensis (MACHADO et al, 2006). This is a review of recent studies on the occurrence of Ehrlichia species in domestic and wild animals, ticks and humans in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary investigation of Ehrlichia species was developed in the northern and southeastern regions of Brazil, including various tick species, humans, dogs, and capybaras, but no Ehrlichia DNA was found in human samples (Labruna et al 2007). In contrast, ehrlichial DNA compatible with Ehrlichia chaffeensis and Ehrlichia ewingii were reported in animal blood samples in Brazil (Machado et al 2007, Oliveira et al 2009. A previous report from Pará State revealed an overall canine seroprevalence of 16.2% for E. canis (Spolidorio et al 2013) Brazilian spotted fever (BSF), a rickettsial disease caused by Rickettsia rickettsii, is the most important tick-borne zoonosis in Brazil, where the disease has been reported since 1929 (Piza et al 1932).…”
Section: Introductionmentioning
confidence: 99%